Foundations and Challenges of the Lula Government’s Foreign Policy - Luis Fernandes (Revista CIDOB d'Afers Internacionals, 2004)
One of the most innovative dimensions of the Lula Government in the first year of its mandate has been the direction its foreign policy has taken. This article analyses the elements of continuity and change in this policy. To do so, the text first divides the country’s foreign policy into State policy and Government policy. Then, it analyses how the traditional position of Brazilian diplomacy in defence of multilateralism has combined, in the current Government,with the understanding that the processes of multi-polarisation currently under way in the international system constitute the most favourable course for defending and expanding Brazil’s margin of independence in the world. The text debates the way in which this orientation has led the Government to strengthen its relations with different poles of power in the international system and to give real priority to the economic and political integration of South America.Finally, it calls attention to the tensions existing between the new orientation of Brazilian foreign policy and the orthodox profile of the policy of macroeconomic stabilisation adopted by the Government to fight the foreign exchange crisis which existed at the beginning of its mandate.